Five-year safety of tildrakizumab in patients with moderate-to-severe psoriasis from two phase 3 trials (reSURFACE 1 and reSURFACE 2): number needed to harm for occurrence of adverse events of special interest - Alexander Egeberg; Denis Jullien; Kristian Gaarn Du Jardin; Diamant Thaçi (Journal of Dermatological Treatment, 2023)
Background Five-year tildrakizumab safety data have been reported as exposure-adjusted incidence rates (EAIRs) of patients with events per 100 patient-years (PYs) of exposure. Objectives To present 5-year safety data from reSURFACE 1/2 phase 3 trials as EAIRs of events per 100 PYs of exposure, and the number needed to harm (NNH) for one adverse event of special interest (AESI) to occur. Methods Pooled analysis from two randomized controlled trials in patients with moderate-to-severe plaque psoriasis (n = 1800). PSOLAR registry was used as safety reference data for NNH estimation. Results Rates of AESI with tildrakizumab were comparable with rates reported in PSOLAR. The NNH for one-year severe infection occurrence was 412 with tildrakizumab 200 mg, and negative for tildrakizumab 100 mg due to lower rates in reSURFACE trials; the NNH for malignancy was 990 for one year with tildrakizumab 100 mg (negative for tildrakizumab 200 mg); and the NNH for major adverse cardiovascular events was 355 for one year with tildrakizumab 200 mg (negative for tildrakizumab 100 mg). Conclusion Tildrakizumab demonstrated a favorable safety profile over 5 years with low rates of AESI, comparable to those of the PSOLAR. Consequently, the NNH for AESI with tildrakizumab were very high or negative due to lower event rates for tildrakizumab.